The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ani10081347
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA8220 Sponges MiR-8516 to Regulate Cell Viability and Milk Synthesis via Ras/MEK/ERK and PI3K/AKT/mTOR Pathways in Goat Mammary Epithelial Cells

Abstract: Circular RNAs (circRNAs), which are considered a large class of endogenous noncoding RNAs, function as regulators in various biological procedures. In this study, the function and molecular mechanisms of circRNA8220 in goat mammary epithelial cells (GMECs) were explored. CircRNA8220 could spong miR-8516 and block the function of miR-8516 by binding to the target site of miR-8516 a negative feedback relationship existed between circRNA8220 and miR-8516. Stanniocalcin 2 (STC2) was a target gene of miR-8516. circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…The purpose of this research was to ascertain the signaling pathways that regulated cell proliferation and apoptosis through the FBXO18/circRNA211/miR-431/CSF1 axis. There was substantial evidence demonstrating that MAPK signaling pathway is involved in cell physiological activity [6,7,27,28]. In this study, overexpression circRNA211 or FBXO18 activated Ras proteins, which in turn triggered downstream phosphorylation levels of Raf, MEK, and ERK proteins.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The purpose of this research was to ascertain the signaling pathways that regulated cell proliferation and apoptosis through the FBXO18/circRNA211/miR-431/CSF1 axis. There was substantial evidence demonstrating that MAPK signaling pathway is involved in cell physiological activity [6,7,27,28]. In this study, overexpression circRNA211 or FBXO18 activated Ras proteins, which in turn triggered downstream phosphorylation levels of Raf, MEK, and ERK proteins.…”
Section: Discussionmentioning
confidence: 65%
“…CircRNAs may act as miRNA sponges to regulate the expression of miRNAs, which regulated the expression of target gene indirectly [3]. Although circRNAs have pleiotropic roles in a variety of biological processes including regulation of myoblasts differentiation in bovine [4], embryo implantation in mouse [5], and milk synthesis in goats [6,7], but their contribution to the formation of RE remains largely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a better understanding of the molecular mechanisms of mammary epithelial cell development is essential to obtain economic benefits. It has been observed that circRNAs can regulate proliferation and viability of goat mammary epithelial cells through their corresponding miRNAs ( Liu et al, 2020a ; Zhu et al, 2020 ). Analogous studies ( Liu et al, 2020b ) on the effect of circHIPK3 on the proliferation and differentiation of BMECs have been performed with cattle.…”
Section: Circular Rnasmentioning
confidence: 99%
“…Milk proteins were mentioned previously in the micRNA section, and corresponding studies have also been reported on circRNAs. For example, Zhu et al (2020) investigated the function and molecular mechanism of circRNA8220 in GMECs and found that there is a circRNA8220/miR-8516/STC2 pathway that promotes the synthesis of ß-casein. Liu et al (2020a) conducted similar studies that suggested that circ016910 acts as a sponge for miR-574-5p and reduces ß-casein secretion by GMECs.…”
Section: Circular Rnasmentioning
confidence: 99%
“…On the one hand, some studies have shown that cir-cRNAs play an important role in regulating the lactation of livestock [3][4][5]. Some studies detected a total of 37,818 circRNAs in goat breast tissue, of which 864 circRNAs were differentially expressed, 611 were upregulated, and 253 were down-regulated [6], so they speculated that these circRNAs may be related to breast development and lactation.…”
Section: Introductionmentioning
confidence: 99%